2008
DOI: 10.1088/1742-6596/112/3/032025
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic pulses at short-pulse laser facilities

Abstract: Electromagnetic Pulse (EMP) is a known issue for short-pulse laser facilities, and will also be an issue for experiments using the advanced radiographic capability (ARC) at the National Ignition Facility (NIF). The ARC diagnostic uses four NIF beams that are compressed to picosecond durations for backlighting ignition capsules and other applications. Consequently, we are working to understand the EMP due to high-energy (MeV) electrons escaping from targets heated by short-pulse lasers. Our approach is to measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 4 publications
3
37
0
Order By: Relevance
“…An advanced diagnostic system planned for NIF, the Advanced Radiographic Capability (ARC), requires shorter pulse durations in the 1 to 10 ps range. Based on results presented here and data from our work at the short-pulse Titan laser facility [5,6], we expect the EMP on NIF to increase significantly during ARC operation. We fielded similar EMP sensors in NIF's target bay and chamber that we used earlier on Titan.…”
Section: Introductionmentioning
confidence: 70%
See 2 more Smart Citations
“…An advanced diagnostic system planned for NIF, the Advanced Radiographic Capability (ARC), requires shorter pulse durations in the 1 to 10 ps range. Based on results presented here and data from our work at the short-pulse Titan laser facility [5,6], we expect the EMP on NIF to increase significantly during ARC operation. We fielded similar EMP sensors in NIF's target bay and chamber that we used earlier on Titan.…”
Section: Introductionmentioning
confidence: 70%
“…However, it is not possible to completely shield any diagnostic and still obtain the needed data. In addition, our work on the Titan short-pulse laser showed that the EMP can extend out to higher frequencies (5 GHz and above) [5,6], which is higher than NIF's original design specification for shielding. This provided motivation to measure EMP on NIF prior to full energy operation to measure energy scaling and to also determine if some targets produced larger EMP.…”
Section: Emp At Nifmentioning
confidence: 81%
See 1 more Smart Citation
“…During this process, the ps and ns laser pulses generated quite different ion emission current densities, leading to up to 100 MeV by sub-picosecond laser plasma [6]. On the other hand, Brown et al [7] also reported that the EMP signals collected at Lawrence Livermore National Laboratory mainly covered the frequency domains from several hundreds of MHz to several GHz. Chen et al [8] reported the microwave emission generated by a laser pulse incident on a metallic disc surface had a frequency ranges from 0.5 GHz to 4 GHz.…”
Section: Photonic Sensors 250mentioning
confidence: 99%
“…With the advent of petawatt lasers and MJ laser facilities the issue of EMP became of considerable practical interest, because such pulses strongly interfere with the electronics used to collect data and manipulate targets and hence pose a serious threat to safe and reliable execution of experiments. Therefore a dedicated effort was made to study the EMP effect at facilities such as Vulcan, Titan, Omega, NIF, LMJ and other (Mead et al, 2004;Raimbourg, 2004;Stoeckl et al, 2006;Remo et al, 2007;Brown et al, 2008; Bourgade et al, 2008; Eder et al., 2009; Brown et al, 2010; Eder et al, 2010;Chen et al, 2011;Bateman & Mead, 2012;Brown et al, 2012;Brown et al, 2013;). Pulses of 100's ns duration and electric fields of 100's kV/m strength were recorded.…”
mentioning
confidence: 99%